Quality of Life as an Useful Indicator for Decision-Making Processes of Public Administration at the Regional Level - Kasáková, Tetiana (Univerzita Pardubice, 2020)
Determining the level of quality of life plays an important role in the governance process of socioeconomic development of the country. The relevance of this issue is also the fact that with proper measurement, based on both objective and subjective statistical indicators, there will be an opportunity to determine the strategy of development of the society, the level of the economic wellbeing of the population, as well as potential of human possibilities. This dissertation deals with the quality of life evaluation and its impact on regional development and human needs as a whole. This work is supposed to show an appropriate way to increase the dynamics of the quality of life in Ukraine, using the image of seven countries with common geographical proximity and a similar history of the recent 50 years. The main subject of the research is the particular indicators of assessing the quality of life used in the framework of various approaches. The recommendations to improve the quality of life in Ukraine using the experience of other countries were developed as the main result of the dissertation thesis.
Keywords: kvalita života; životní spokojenost; životní podmínky; souhrnný indikator; hodnocení kvality života; quality of life; life satisfaction; living conditions; aggregate indicator; life quality assessment